ANALYSIS OF LIFE INSURANCE PRODUCTS FOR DIFFERENT RISK ATTITUDE OF HIGH NET WORTH INDIVIDUALS IN INDONESIA - , Dian Ardhini Hapsari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Insurance is the most important device for risk transfer. The purpose of insurance is to compensate for financial loss. For high net worth individual, those having investable assets (financial assets not including primary residence) in excess of 10 billion Rupiah, insurance is very important. HNWIs face personal risk and although they live lavishly they are not free from risk. Some even say the more they have, the more they will suffer if the assets are lost from unexpected events. There are three types of risk attitude: risk averse, risk neutral and risk seeker. Different risk attitude will determine different decisions in financial planning whether in investment or protection decision. Life insurance is the basic protection for families. There are three type of life insurance: term life, whole life and endowment life. This research aimed to analyze which life insurance products will give best benefits to HNWIs and categorizes based on their risk attitudes. Two life insurance companies was taken as samples for this research. They are the biggest assets company from both government and private own companies. There are 15 products that have been analyzed and classification has been made for those. There is no match classification between risk attitude of client with the type of life insurance product (whole life, term life or endowment). Each type of products are different based on insurance coverage and also investment allocation in endowment product. Each life insurance product has different characteristic that match with different risk attitude of HNWIs.